Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1997
DOI: 10.1183/09031936.97.10122892
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of depth and composition of airway surface liquid

Abstract: R Re eg gu ul la at ti io on n o of f d de ep pt th h a an nd d c co om mp po os si it ti io on n o of f a ai ir rw wa ay y s su ur rf fa ac ce e l li iq qu ui id dThe airways are lined with a film of fluid, which is 5-20 µm deep in healthy individuals. This fluid is believed to consist of two phases [1]. A watery fluid of low viscosity, the "periciliary sol" surrounds the cilia. Above this lies a viscous mucous gel. The cilia are able to beat in the sol. Their tips contact the underside of the mucous blanket … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(41 citation statements)
references
References 31 publications
1
40
0
Order By: Relevance
“…The PCL in healthy conditions is ∼ 7 μm thick [92,93]. The thickness of the luminal mucus layer varies throughout the respiratory tract, increasing from distal to proximal airways [93,94].…”
Section: Mucociliary Clearancementioning
confidence: 99%
“…The PCL in healthy conditions is ∼ 7 μm thick [92,93]. The thickness of the luminal mucus layer varies throughout the respiratory tract, increasing from distal to proximal airways [93,94].…”
Section: Mucociliary Clearancementioning
confidence: 99%
“…Existence of non-motile cilia is discussed in cells without central double tubules acting as sensory antenna. Cilia are covered by a 10–15 µm thick layer of mucus, filling also the spaces between cilia [8]. In respiratory mucosa, goblet cells and seromucous glands in the adjacent connective tissue are typically found.…”
Section: Anatomical and Histological Structures Of The Respiratory mentioning
confidence: 99%
“…It is suggested that T-helper type 2 lymphocytes, and the cytokines that they produce, in conjunction with reactive oxygen species (ROS) and reactive nitrogen species (RNS) produced by inflammatory and epithelial cells, contributed as the key mediators of the chronic airway inflammation of asthma (Calhoun et al, 1992;Horwitz and Busse, 1995;Renauld, 2001;Zhou et al, 2001). The airway surface is covered by a thin fluid layer, termed as the airway surface liquid and this acts as a barrier to protect the underlying epithelium (Widdicombe, 2002). The identification of secreted proteins in this fluid may be important in understanding the etiology of asthma.…”
Section: Inflammatory and Allergy Diseases Asthmamentioning
confidence: 99%